2019
DOI: 10.3389/fpsyg.2019.00724
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Values About Music in Early Childhood Education and Care: Perspectives From Practitioners

Abstract: This paper reports the findings of a study that aimed to identify the music beliefs and values of educators in early childhood education and care settings in Australia. The aims of the study were 2-fold: to adapt and pilot a survey of music beliefs and values which might be implemented subsequently nationally in childcare settings; and, secondly, to identify the music beliefs and values held by early childhood and care educators concerning music in children's learning. The research questions that guided this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 70 publications
1
18
1
6
Order By: Relevance
“…First, most kindergarten teachers have limited personal experiences with music and movement prior to their formal teacher preparation. For example, in a study conducted in Australia, few kindergarten teachers had previously participated in extracurricular music and movement activities, or held formal qualifications, or engaged in music-making in their personal time (Barrett, Flynn et al, 2019). These findings are concerning, as there is strong evidence that teachers' active music and movement engagement leads to positive beliefs about the educational value of this learning area and influences teachers' ideologies positively (Young, 2007) and contributes to enhancing their sense of efficacy and pedagogical competencies (Burak, 2019).…”
Section: Literature Review Kindergarten Teachers' Educational Experiences With Music and Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most kindergarten teachers have limited personal experiences with music and movement prior to their formal teacher preparation. For example, in a study conducted in Australia, few kindergarten teachers had previously participated in extracurricular music and movement activities, or held formal qualifications, or engaged in music-making in their personal time (Barrett, Flynn et al, 2019). These findings are concerning, as there is strong evidence that teachers' active music and movement engagement leads to positive beliefs about the educational value of this learning area and influences teachers' ideologies positively (Young, 2007) and contributes to enhancing their sense of efficacy and pedagogical competencies (Burak, 2019).…”
Section: Literature Review Kindergarten Teachers' Educational Experiences With Music and Movementmentioning
confidence: 99%
“…The low provision and limited usefulness of music and movement educational experiences (including extracurricular activities, preservice courses, and in-service PD) lead to numerous negative consequences. Many kindergarten teachers neither understand nor value the key role that music and movement plays in children's holistic development (Barrett, Flynn et al, 2019;Kim & Kemple, 2011). Furthermore, many teachers have low confidence and sense of efficacy regarding music and movement teaching (Swain & Bodkin-Allen, 2014), often the lowest among all art forms (Koutsoupidou, 2010), which may result in anxiety and feelings of insecurity (Neokleous, 2010).…”
Section: Literature Review Kindergarten Teachers' Educational Experiences With Music and Movementmentioning
confidence: 99%
“…and in particular pro-social skills, particularly when the musical activities are shared rather than solitary; (Williams, 2015). It is also noted that music influences emotions (Barrett, Brown and Welch, 2019;Juslin &Vastfjall, 2008;Sloboda, O'Neill & Ivaldi, 2001). Sloboda (2011) for example found that listening to music helps with emotions by distracting from a distressing situation or helping individuals to think about the situation in a rational way.…”
Section: Arts In Health Settingsmentioning
confidence: 99%
“…It is no surprise, therefore, that-given this curricular bias towards a 'core curriculum'-the preservice and in-service preparation of nursery and Primary teachers often provides limited opportunities for engagement in arts pedagogy, including music. This inadequacy in professional experience is reported in England (cf Hennessy, 2010;Poulter & Cook, 2020;Welch & Henley, 2014), as well as elsewhere in the world, such as Scotland (Bhachu, 2019), Australia (Barrett, Flynn, Brown, & Welch, 2019;Letts, 2015) and Singapore (Chua & Welch, 2019).…”
Section: Introductionmentioning
confidence: 97%